Peningkatan Prestasi Belajar Bahasa Indonesia Dengan Strategi Pembelajaran Lesson Study Pada Siswa Kelas VII D SMPN 3 Ponorogo - Dhea Vica Nuraini; Panji Kuncoro Hadi; Titik Dwi Astuti (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The purpose of this study is to be able to describe the improvement of Indonesian language learning achievement with the application of lesson study learning strategies in class VII D students of SMPN 3 Ponorogo in the 2022/2023 academic year. The approach in this research is descriptive qualitative. The process of Classroom Action Research (PTK) was carried out using the model of Kemmis and Mc.Taggart. The research subjects used were students in class VII D SMPN 3 Ponorogo, totalling 32 students. Techniques used for data collection were observation and interview. The lesson study learning strategy for Indonesian language learning material on summarising fiction and non-fiction books was carried out with three stages, namely plan, do, and see which were carried out in three cycles. The results of data obtained the results of learning completeness by students who were classically "achieved". The ability to summarise fiction and non-fiction books can be improved through the learning process by applying lesson study learning strategies. The increase in students' learning completeness in each cycle, namely in cycle 1 had a percentage of 71.86% (not yet achieved), cycle 2 was 81.25% (not yet achieved), and cycle 3 was 93.75% (achieved). Keyword: Learning Achievement; Classroom Action Research; Lesson Study